2005
DOI: 10.1104/pp.105.059477
|View full text |Cite
|
Sign up to set email alerts
|

Immunopurification of Polyribosomal Complexes of Arabidopsis for Global Analysis of Gene Expression

Abstract: Immunoaffinity purification of polyribosomes (polysomes) from crude leaf extracts of Arabidopsis (Arabidopsis thaliana) was achieved with transgenic genotypes that overexpress a translational fusion of a ribosomal protein (RP) with a His 6 -FLAG dual epitope tag. In plants with a cauliflower mosaic virus 35S:HF-RPL18 transgene immunopurification with anti-FLAG agarose beads yielded 60-Svedberg ribosomal subunits, intact 80-Svedberg monosomes and polysomes. Sucrose density gradient fractionation of the purified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
237
0
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 226 publications
(251 citation statements)
references
References 57 publications
1
237
0
8
Order By: Relevance
“…It has been reported that the percentage of particular mRNAs bound to polysomes in A. thaliana varies typically from 35 to 85% (30). For the AtFtsH10 transcript, this value was 59% (30).…”
Section: Identification Of Atftsh3 and Atftsh10mentioning
confidence: 90%
See 1 more Smart Citation
“…It has been reported that the percentage of particular mRNAs bound to polysomes in A. thaliana varies typically from 35 to 85% (30). For the AtFtsH10 transcript, this value was 59% (30).…”
Section: Identification Of Atftsh3 and Atftsh10mentioning
confidence: 90%
“…For the AtFtsH10 transcript, this value was 59% (30). Taking into consideration the above and the fact that the steady-state level of the FtsH10 transcript is similar in ftsh3 and wild type plants, but almost twice as many molecules of this transcript are bound to polysomes in ftsh3, we conclude that practically all AtFtsH10 transcripts are associated with polysomes in the ftsh3 mutant.…”
Section: Identification Of Atftsh3 and Atftsh10mentioning
confidence: 96%
“…The transgenic A. thaliana 35S:HF-RPL18B line 12-2-4 (ecotype Col-0) was used in this study (1). Seedlings were grown on solid media [0.43% (wt/vol) Murashige and Skoog salts, 1% (wt/vol) sucrose] at 23°C under a 16-h light (80 μE·m −2 ·s −1 ) and 8-h dark cycle for 7 d. Hypoxia was imposed as described previously (15) for 2 h under low light (7 μE·m −2 ·s −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…A typical way to assess translation is to isolate transcripts in association with one or more ribosomes (i.e., polysomes) by differential centrifugation. To facilitate the capture of ribosome-associated mRNA, we developed a method for translating ribosome affinity immunopurification (TRAP) incorporating FLAG-tagged ribosomal protein L18 (RPL18) into functional ribosomes in the model plant Arabidopsis thaliana (1). Two advantages of TRAP are that it reduces contamination of polysome preparations with mRNA-ribonucleoprotein (mRNP) complexes of similar density and can be used to obtain mRNAs from subpopulations of cells of a multicellular organ or tissue in plants (2,3), as well as in mammals and insects (4,5).…”
mentioning
confidence: 99%
“…To date, analyses of the Arabidopsis mitochondrial proteome have only identified five mitochondrial r-proteins (S4, L3, L7/L12, L22, and L25) (Heazlewood et al 2004;Heazlewood and Millar 2005). An approach that may unambiguously answer this question would be to epitope tag S15a proteins (Types I and II) in a manner that facilitated immunoprecipitation of the ribosome complex as shown for cytosolic RPL18 and RPL23 (Zanetti et al 2005). The coimmunoprecipitated proteins could then be subsequently analyzed by mass spectrometry to determine the coassociated proteins.…”
Section: Subcellular Location Of Type II S15amentioning
confidence: 99%